From capsules to nutlets—phylogenetic relationships in the Boraginales. (11th November 2013) - Weigend, Maximilian; Luebert, Federico; Gottschling, Marc; Couvreur, Thomas L.P.; Hilger, Hartmut H.; Miller, James S.
Abstract Multiple family‐level subdivisions of Boraginales have been proposed in the past. The relationships of several constituent genera have been enigmatic, including Codon (Codonaceae), Hoplestigma (Hoplestigmataceae), Pholisma (Lennoaceae), Vahlia (Vahliaceae), and Wellstedia (Wellstediaceae), all of which are included in the present study. We present a molecular analysis with four chloroplast loci, including 89 ingroup taxa and a broad outgroup sampling in the asterids. The genus Vahlia is excluded from Boraginales and appears to represent an early branching lineage of Lamiales. The study provides a well supported topology for the relationships within Boraginales, including all of the genera with previously unclear relationships. Within Boraginales, two major clades are recognized, with "herbaceaous" Boraginales I resolved as [Codonaceae, [Wellstediaceae, [Boraginaceae]]] and "woody" Boraginales II resolved as [Hydrophyllaceae I, [Hydrophyllaceae II, [Heliotropiaceae, [Cordiaceae, [Ehretiaceae, Lennoaceae]]]]. A close relationship between Ehretiaceae and Lennoaceae is well supported, but the exact placement of Lennoaceae remains unresolved. The Cordiaceae lineage includes the monotypic genus Coldenia and the aberrant western and central African genus Hoplestigma. Woody Boraginales II are retrieved in two highly supported clades. Hydrophyllaceae are retrieved in two separate clades, but with poor support. There appear to be clear morphological progressions in vegetative, floral, and fruit morphology in both major Boraginales lineages. Thus capsular fruits are found in the first branching lineages of both clades, whereas reduced seed numbers in indehiscent fruits predominate in the more derived phylogenetic positions. Based on these results, we advocate the recognition of eight morphologically well defined clades in the order, namely Boraginaceae s.str., Codonaceae, Cordiaceae (incl. Coldenia and Hoplestigmataceae), Ehretiaceae (incl. Lennoaceae), Heliotropiaceae, Hydrophyllaceae I and Hydrophyllaceae II, and Wellstediaceae.